National-scale analysis of extinction risk correlates in Italian flowering plants - Angelino Carta; Margherita Gioria; Elena Zappa; Mariacristina Villani; Simonetta Bagella; Sara Magrini; Annalisa Santangelo; Emmanuele Farris; Giulia Calderisi; Donatella Cogoni; Maria Silvia Pinna; Gianpietro Giusso del Galdo; et al. (Biological Conservation, 2026)

Hydrogeological and vegetational assessment of Fontanili (lowland springs) in Southern Turin Po Plain (Italy): conservation and environmental impacts - Federico Emanuel Franco; Sara Giammario; Marica Tumminello; Maria Rita Minciardi; Concita Daniela Spada; Simone Ciadamidaro; Domenico Antonio De Luca; Elena Egidio; Daniele Cocca; Manuela Lasagna (Sustainable Water Resources Management, 2026)
This study presents the hydrogeological and vegetational context of lowland springs -known in Italian as risorgive or fontanili - in a sector of the southern Po Plain near Turin (north-western Italy). Despite their important ecological role, these springs remain understudied, particularly regarding the effects of climate change and human activities. Not included in Italy’s environmental protection regulations and often poorly maintained, they require accurate identification and characterisation to support monitoring and management by local authorities. This study adopts a multidisciplinary approach, combining hydrogeological analysis with vegetation surveys, an integration rarely found in recent literature. Fontanili in the study area were mapped, and two field campaigns were conducted in summer and autumn 2022. A total of 92 springs was identified, of which only 26 were active during the study period due to prolonged drought. Hydrochemical and piezometric analyses of the shallow aquifer were performed, alongside vegetation surveys carried out at 28 springs in autumn 2022 and spring 2023. Hydrochemical data revealed a contrast between groundwater and surface water characteristics, with calcium bicarbonate prevailing in groundwater and calcium sulphate in surface water. Vegetation data indicated a loss of hygrophilous species linked to water scarcity, along with an increase in invasive alien species. The results highlight the vulnerability of these ecosystems and the urgent need for their conservation. The study aims to raise awareness, promote further research, and encourage local authorities to take concrete action for the protection of these unique lowland spring habitats.

Mapping the advancements in floristic knowledge of Italy (2005–2025) - Gianniantonio Domina; Gianluigi Bacchetta; Fabrizio Bartolucci; Marco D’Antraccoli; Lorenzo Peruzzi; Adriano Stinca; Alessandro Alessandrini; Liliana Bernardo; Francesco Boscutti; Daniela Bouvet; Maurizio Bovio; Giacomo Calvia; et al. (Plant Biosystems, 2026)
Based on the evaluation of 3,902 local floristic references published between 2005 and 2025, an update to the floristic knowledge map of Italy is presented. To measure the progress in floristic knowledge across Italy’s administrative regions, the ‘Index of Floristic Knowledge Advancement’ (IFA) is proposed here. This index categorizes regions based on the proportion of potential improvement that has actually been achieved. Results showed an improvement in knowledge, most notably for Northern and Central Italy. Emilia-Romagna emerged as the most comprehensively documented region with the highest IFA value (0.81), followed by Lombardia (0.60), Friuli-Venezia Giulia (0.54), Trentino-Alto Adige and Veneto (0.53). In central Italy, Lazio (0.50), Sardegna (0.45) and Toscana (0.36) registered the highest scores. Over the past twenty years, 453 specific and subspecific taxa have been described from the Italian territory, the majority of which (443) are Italian endemics. Hieracium is the most represented genus (147 taxa). The marked progress documented is likely due to the accelerated impact of coordinated scientific projects, citizen science programs, the development of digital databases, and an increased focus on taxonomic research.

Microplastics and Nanoplastics in Cardiovascular Disease: An Emerging Cardiovascular Risk Factor - Alberto Polimeni; Domenico Simone Castiello; Rossella Quarta; Tommaso Gori; Giovanni Martino; Letizia Rosa Romano; Federica Meringolo; Giovanni Lopes; Masakazu Yasuda; Ciro Indolfi; Antonio Curcio (Cardiovascular Toxicology, 2026)
Microplastics and nanoplastics (MNPs) have become pervasive contaminants in air, water, and food, leading to continuous human exposure. Contrary to the long-standing assumption that these particles are biologically inert, accumulating evidence now shows that MNPs cross epithelial and endothelial barriers, circulate systemically, and accumulate in cardiovascular tissues. Experimental, translational, and early clinical studies demonstrate that some MNPs can induce oxidative stress, endothelial dysfunction, mitochondrial injury, immune activation, and coagulation pathway dysregulation, mechanisms that converge on atherosclerotic development and progression, plaque destabilization, atherothrombosis, and cardiac remodeling. Recent human data identifying MNPs in carotid and coronary plaques, arterial specimens, thrombi, and cardiac tissues provide direct proof-of-concept for their cardiovascular involvement. These findings position MNPs as an emerging cardiovascular risk factor, with implications for prevention, patient risk stratification, and environmental health policy. Major knowledge gaps remain, including the absence of standardized biomarkers of exposure, dose–response quantification, and longitudinal clinical cohorts. Recognizing environmental plastics as cardiovascular toxins demands urgent, multidisciplinary investigation and integration of environmental exposure into cardiovascular disease prevention frameworks. Graphical Abstract Overview of exposure routes and subsequent pathophysiological mechanisms of microplastics and nanoplastics leading to cardiovascular disease scenarios.

Monsoon variability and high latitude climate signals in the Central Mediterranean at the Pliocene- Pleistocene transition: The Gelasian stratotype section (Monte San Nicola, Sicily) [Global and Planetary Change, volume 249, 104788]: Comment - Elena Zanola; Sergio Bonomo; Alessandro Incarbona; Telemaco Tesei; Agata Di Stefano; Patrizia Ferretti; Eliana Fornaciari; Simone Galeotti; Patrizia Macrì; Isabella Raffi; Teresa Rodrigues; Fabio Speranza; et al. (Global and Planetary Change, 2025)

ITV-net: a dataset of intraspecific leaf traits data across major Italian habitats - Stefano Chelli; Alessandro Bricca; Francesco Petruzzellis; Enrico Tordoni; Giacomo Calvia; Alicia T.R Acosta; Giovanni Bacaro; Eleonora Beccari; Liliana Bernardo; Gianmaria Bonari; Rossano Bolpagni; Francesco Boscutti; et al. (Plant Biosystems, 2025)

The reintroduction of Apennine chamois in the Majella National Park: An evaluation of long-term results - Antonio Antonucci; Alessandro Asprea; Roberta Chirichella; Simone Angelucci; Giovanna Di Domenico; Marco Apollonio (Journal for Nature Conservation, 2025)

A new technology for a novel clinical approach in a dog with a complex vascular anomaly: the “extended reality” - Simone Cupido; Federica Valeri; Stefano Nicoli; Paolo Bargellini; Domenico Caivano; Francesco Birettoni; Andrea Bortolotti; Mark Rishniw; Francesco Porciello (Veterinary Research Communications, 2025)
Extended reality includes both virtual and augmented realities. In virtual reality objects are rendered in an artificial environment where the user can move and interact with a head mounted display. In augmented reality virtual objects are superimposed to real environment enriching it via a head mounted display. In human medicine these technologies have been already used for educational surgical purposes, but remain relatively unknown in veterinary medicine. We report a case of a 1-year-old, female, French bulldog presented for exercise intolerance and dyspnea. Echocardiography showed signs of left ventricular enlargement with reduced fractional shortening and turbulent flow distal to the pulmonary artery bifurcation. Computed tomography revealed a complex vascular network comprising the descending aorta and left pulmonary artery resembling a patent ductus arteriosus. Virtual reality was used for the surgical planning and a left thoracotomy was performed to close the abnormal vessel at the level of the entrance in the left pulmonary artery with augmented reality assistance. No complications were reported during or after the surgery and the dog completely recovered. Echocardiographic findings 3 days, 1 month and 18 months after the surgery demonstrated absence of residual flow and improving ventricular dimensions. To our knowledge this report documents the first use of extended reality for the visualization, planning and execution of the surgical correction of a complex vascular defect in veterinary medicine.

Corrigendum to “Food web analysis shows an exacerbated dependence of zooplankton on detritus in oligotrophic systems due to ocean warming” [Prog. Oceanogr. 231 (2025) 103389] - Luca Russo; Matteo Loschi; Daniele Bellardini; Roberta Congestri; Michael W. Lomas; Simone Libralato; Domenico D’Alelio (Progress in Oceanography, 2025)

Food web analysis shows an exacerbated dependence of zooplankton on detritus in oligotrophic systems due to ocean warming - Luca Russo; Matteo Loschi; Daniele Bellardini; Roberta Congestri; Michael W. Lomas; Simone Libralato; Domenico D’Alelio (Progress in Oceanography, 2025)

Correction: A pre‑whitening with block‑bootstrap cross‑correlation procedure for temporal alignment of data sampled by eddy covariance systems - Domenico Vitale; Gerardo Fratini; Carole Helfter; Lukas Hortnagl; Kukka-Maaria Kohonen; Ivan Mammarella; Eiko Nemitz; Giacomo Nicolini; Corinna Rebmann; Simone Sabbatini; Dario Papale (Environmental and Ecological Statistics, 2024)

A pre-whitening with block-bootstrap cross-correlation procedure for temporal alignment of data sampled by eddy covariance systems - Domenico Vitale; Gerardo Fratini; Carole Helfter; Lukas Hortnagl; Kukka-Maaria Kohonen; Ivan Mammarella; Eiko Nemitz; Giacomo Nicolini; Corinna Rebmann; Simone Sabbatini; Dario Papale (Environmental and Ecological Statistics, 2024)
The eddy covariance (EC) method is a standard micrometeorological technique for monitoring the exchange rate of the main greenhouse gases across the interface between the atmosphere and ecosystems. One of the first EC data processing steps is the temporal alignment of the raw, high frequency measurements collected by the sonic anemometer and gas analyser. While different methods have been proposed and are currently applied, the application of the EC method to trace gases measurements highlighted the difficulty of a correct time lag detection when the fluxes are small in magnitude. Failure to correctly synchronise the time series entails a systematic error on covariance estimates and can introduce large uncertainties and biases in the calculated fluxes. This work aims at overcoming these issues by introducing a new time lag detection procedure based on the assessment of the cross-correlation function (CCF) between variables subject to (i) a pre-whitening based on autoregressive filters and (ii) a resampling technique based on block-bootstrapping. Combining pre-whitening and block-bootstrapping facilitates the assessment of the CCF, enhancing the accuracy of time lag detection between variables with correlation of low order of magnitude (i.e. lower than $$-1$$ - 1 ) and allowing for a proper estimate of the associated uncertainty. We expect the proposed procedure to significantly improve the temporal alignment of the EC time-series measured by two physically separate sensors, and to be particularly beneficial in centralised data processing pipelines of research infrastructures (e.g. the Integrated Carbon Observation System, ICOS-RI) where the use of robust and fully data-driven methods, like the one we propose, constitutes an essential prerequisite.

Human Campylobacter spp. infections in Italy - Verena Zerbato; Stefano Di Bella; Riccardo Pol; Roberto Luzzati; Gianfranco Sanson; Simone Ambretti; Stefano Andreoni; Richard Aschbacher; Mariano Bernardo; Alessandra Bielli; Gioconda Brigante; Marina Busetti; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Intraspecific variability of leaf form and function across habitat types - Giacomo Puglielli; Alessandro Bricca; Stefano Chelli; Francesco Petruzzellis; Alicia T. R. Acosta; Giovanni Bacaro; Eleonora Beccari; Liliana Bernardo; Gianmaria Bonari; Rossano Bolpagni; Francesco Boscutti; Giacomo Calvia; et al. (Ecology Letters, 2024)
Trait‐based ecology has already revealed main independent axes of trait variation defining trait spaces that summarize plant adaptive strategies, but often ignoring intraspecific trait variability (ITV). By using empirical ITV‐level data for two independent dimensions of leaf form and function and 167 species across five habitat types (coastal dunes, forests, grasslands, heathlands, wetlands) in the Italian peninsula, we found that ITV: (i) rotated the axes of trait variation that define the trait space; (ii) increased the variance explained by these axes and (iii) affected the functional structure of the target trait space. However, the magnitude of these effects was rather small and depended on the trait and habitat type. Our results reinforce the idea that ITV is context‐dependent, calling for careful extrapolations of ITV patterns across traits and spatial scales. Importantly, our study provides a framework that can be used to start integrating ITV into trait space analyses.

Multi-locus sequence typing and in vitro antimicrobial resistance of equine Streptococcus equi subspecies zooepidemicus strains - Francesca Paola Nocera; Loredana Capozzi; Domenico Simone; Francesca Pizzano; Valentina Iovane; Angelica Bianco; Antonio Parisi; Luisa De Martino (Veterinary Research Communications, 2024)

High-resolution climate variability across the Piacenzian/Gelasian boundary in the Monte San Nicola section (Sicily, Italy) - Elena Zanola; Sergio Bonomo; Alessandro Incarbona; Agata Di Stefano; Salvatore Distefano; Patrizia Ferretti; Eliana Fornaciari; Simone Galeotti; Patrizia Macrì; Isabella Raffi; Nadia Sabatino; Fabio Speranza; et al. (Quaternary Science Reviews, 2024)

Reduced complexity debris flow/flood hazard assessment at the southwestern slope of Mt. Omo, L’Aquila municipality, central Italy - Luigi Guerriero; Mirko Francioni; Domenico Calcaterra; Diego Di Martire; Simone Palumbo; Claudia Zito; Nicola Sciarra (Landslides, 2024)

Waste management beyond the COVID-19 pandemic: Bibliometric and text mining analyses - Meisam Ranjbari; Zahra Shams Esfandabadi; Sneha Gautam; Alberto Ferraris; Simone Domenico Scagnelli (Gondwana Research, 2023)

Computational electrophysiology of the coronary sinus branches based on electro-anatomical mapping for the prediction of the latest activated region - Christian Vergara; Simone Stella; Massimiliano Maines; Pasquale Claudio Africa; Domenico Catanzariti; Cristina Demattè; Maurizio Centonze; Fabio Nobile; Alfio Quarteroni; Maurizio Del Greco (Medical & Biological Engineering & Computing, 2022)
This work dealt with the assessment of a computational tool to estimate the electrical activation in the left ventricle focusing on the latest electrically activated segment (LEAS) in patients with left bundle branch block and possible myocardial fibrosis. We considered the Eikonal-diffusion equation and to recover the electrical activation maps in the myocardium. The model was calibrated by using activation times acquired in the coronary sinus (CS) branches or in the CS solely with an electroanatomic mapping system (EAMS) during cardiac resynchronization therapy (CRT). We applied our computational tool to ten patients founding an excellent accordance with EAMS measures; in particular, the error for LEAS location was less than 4 mm. We also calibrated our model using only information in the CS, still obtaining an excellent agreement with the measured LEAS. The proposed tool was able to accurately reproduce the electrical activation maps and in particular LEAS location in the CS branches, with an almost real-time computational effort, regardless of the presence of myocardial fibrosis, even when information only at CS was used to calibrate the model. This could be useful in the clinical practice since LEAS is often used as a target site for the left lead placement during CRT. Graphical abstract Overall picture of the computational pipeline for the estimation of LEAS

Seed germination under osmotic stress across different wild populations of mountain rye ( Secale strictum (C.Presl) C.Presl)) - Graziano Rossi; Filippo Guzzon; Charlotte Bickler; Paolo Cauzzi; Luciano Di Martino; Valter Di Cecco; Gianniantonio Domina; Domenico Gargano; Ilda Vagge; Simone Orsenigo; Jonas V. Müller (Plant Biosystems, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

EUMETNET opens to microwave radiometers for operational thermodynamical profiling in Europe - Rolf Rüfenacht; Alexander Haefele; Bernhard Pospichal; Domenico Cimini; Simone Bircher-Adrot; Myles Turp; Jacqueline Sugier (Bulletin of Atmospheric Science and Technology, 2021)

Conservation status of the Italian flora under the 92/43/EEC ‘Habitats’ Directive - Giuseppe Fenu; Consolata Siniscalco; Gianluigi Bacchetta; Donatella Cogoni; Maria Silvia Pinna; Marco Sarigu; Thomas Abeli; Elena Barni; Fabrizio Bartolucci; Daniela Bouvet; Annalena Cogoni; Fabio Conti; et al. (Plant Biosystems, 2021)

Recovery agenda for sustainable development post COVID-19 at the country level: developing a fuzzy action priority surface - Meisam Ranjbari; Zahra Shams Esfandabadi; Simone Domenico Scagnelli; Peer-Olaf Siebers; Francesco Quatraro (Environment, Development and Sustainability, 2021)
As a response to the urgent call for recovery actions against the COVID-19 crisis, this research aims to identify action priority areas post COVID-19 toward achieving the targets of the sustainable development goals (SDGs) within the 2030 Agenda for Sustainable Development launched by the United Nations (UN). This paper applies a mixed-method approach to map the post-COVID-19 SDGs targets on a fuzzy action priority surface at the country level in Iran, as a developing country, by taking the following four main steps: (1) using a modified Delphi method to make a list of the SDGs targets influenced by COVID-19; (2) using the best–worst method, as a multi-criteria decision-making tool, to weight the COVID-19 effects on the SDGs targets achievement; also (3) to weight the impact of the SDGs targets on the sustainable development implementation; and finally (4) designing a fuzzy inference system to calculate the action priority scores of the SDGs targets. As a result, reduction of poor people proportion by half (SDG 1.2), development-oriented policies for supporting creativity and job creation (SDG 8.3), end the pandemics and other epidemics (SDG 3.3), reduction of deaths and economic loss caused by disasters (SDG 11.5), and financial support for small-scale enterprises (SDG 9.3) were identified as the highest priorities for action, respectively, in the recovery agenda for sustainable development post COVID-19. The provided fuzzy action priority surface supports the UN’s SDGs achievement and implementing the 2030 Agenda for Sustainable Development in Iran. It also serves as a guideline to help the government, stakeholders, and policy-makers better analyze the long-term effects of the pandemic on the SDGs and their associated targets and mitigate its adverse economic, social, and environmental consequences. Graphical abstract

Red list of threatened vascular plants in Italy - Simone Orsenigo; Giuseppe Fenu; Domenico Gargano; Chiara Montagnani; Thomas Abeli; Alessandro Alessandrini; Gianluigi Bacchetta; Fabrizio Bartolucci; Angelino Carta; Miris Castello; Donatella Cogoni; Fabio Conti; et al. (Plant Biosystems, 2021)

Towards the profiling of the atmospheric boundary layer at European scale—introducing the COST Action PROBE - Domenico Cimini; Martial Haeffelin; Simone Kotthaus; Ulrich Löhnert; Pauline Martinet; Ewan O’Connor; Christopher Walden; Martine Collaud Coen; Jana Preissler (Bulletin of Atmospheric Science and Technology, 2020)
The atmospheric boundary layer (ABL) is the layer closest to the Earth’s surface within which most human activities take place. The vertical profile of atmospheric thermodynamic parameters in the ABL impact weather, air quality and climate. However, surface sensor networks and satellite observations do not provide sufficient information on the high temporal variability and strong vertical gradients that occur in the ABL. Thus, the ABL represents an important but rather under-sampled part of the atmosphere. This observational gap currently hampers progress in numerical weather prediction, air quality forecasting and climate assessment. Due to recent technological and methodological advances, ground-based remote sensing instruments are now able to provide high-quality profiles of ABL parameters such as temperature, humidity, wind, aerosol and cloud properties. However, even though state-of-the-art ABL profilers are deployed at numerous sites in Europe, efficient science and technology networking and coordination is still required to exploit this rich dataset effectively. The current lack of data and procedure harmonization often diminishes the potential societal benefits of the existing ABL profiling data. This paper introduces PROBE, a new initiative funded by the European Cooperation in Science and Technology (COST), that aims to broaden the bridge between a wide range of user needs and the science and technology expertise residing in industry and academia, while strengthening and harmonizing methods and procedures to yield higher quality ABL observational data. Here, the challenges, objectives and implementation plan for PROBE are described, highlighting some preliminary results that will be further developed into operational applications during the 4-year duration (2019–2023) of this collaborative project.

Ontogenic succession of thermokarst thaw ponds is linked to dissolved organic matter quality and microbial degradation potential - Sari Peura; Maxime Wauthy; Domenico Simone; Alexander Eiler; Karólína Einarsdóttir; Milla Rautio; Stefan Bertilsson (Limnology and Oceanography, 2020)
Warming climate is thawing the permafrost in arctic and subarctic regions, leading to formation of thermokarst ponds. During the formation and geomorphological succession of these ponds, carbon that has been trapped in frozen soils for thousands of years is hydrologically mobilized and returned to the active carbon cycle. We sampled 12 thermokarst ponds representing three different stages of pond succession to study the potential of microbial communities to metabolize the organic carbon in the water. We investigated the quality of the dissolved organic carbon (DOC) in the water column based on the spectrophotometric and fluorometric properties of the chromophoric dissolved organic matter combined with parallel factor analysis and the potential of the microbial community for degrading these carbon compounds based on genetic markers related to carbon degradation. Our analysis showed a clear difference in the DOC quality across the different developmental stages. In the younger ponds, organic matter quality suggested that it was originating from the degrading permafrost and in the metagenomes collected from these ponds, the normalized abundance of genes related to degradation of carbon compounds was higher. There was also a shift in the degradation potential in the water column of the ponds, with higher potential for organic matter degradation in deeper, anoxic layers. In conclusion, our results show that the DOC quality and the genetic potential of the microbial community for carbon cycling change across the pond ontogeny, suggesting a capacity of the microbial communities to adapt to changing environmental conditions.

Detection of selected pathogens in Apennine wolf (Canis lupus italicus) by a non-invasive GPS-based telemetry sampling of two packs from Majella National Park, Italy - Cristina E. Di Francesco; Camilla Smoglica; Barbara Paoletti; Simone Angelucci; Marco Innocenti; Antonio Antonucci; Giovanna Di Domenico; Fulvio Marsilio (European Journal of Wildlife Research, 2019)

Litter decomposition: effects of temperature driven by soil moisture and vegetation type - Alessandro Petraglia; Cecilia Cacciatori; Stefano Chelli; Giuseppe Fenu; Giulia Calderisi; Domenico Gargano; Thomas Abeli; Simone Orsenigo; Michele Carbognani (Plant and Soil, 2019)

Deregulation of autophagy under hyperglycemic conditions is dependent on increased lysine 63 ubiquitination: a candidate mechanism in the progression of diabetic nephropathy - Paola Pontrelli; Annarita Oranger; Mariagrazia Barozzino; Chiara Divella; Francesca Conserva; Maria Grazia Fiore; Roberta Rossi; Massimo Papale; Giuseppe Castellano; Simona Simone; Luigi Laviola; Francesco Giorgino; et al. (Journal of Molecular Medicine, 2018)

Sub-inhibitory stress with essential oil affects enterotoxins production and essential oil susceptibility in Staphylococcus aureus - Barbara Turchi; Simone Mancini; Luisa Pistelli; Basma Najar; Domenico Cerri; Filippo Fratini (Natural Product Research, 2018)

PCA-based artifact removal algorithm for stroke detection using UWB radar imaging - Elisa Ricci; Simone di Domenico; Ernestina Cianca; Tommaso Rossi; Marina Diomedi (Medical & Biological Engineering & Computing, 2017)

Patient-specific generation of the Purkinje network driven by clinical measurements of a normal propagation - Christian Vergara; Simone Palamara; Domenico Catanzariti; Fabio Nobile; Elena Faggiano; Cesarino Pangrazzi; Maurizio Centonze; Massimiliano Maines; Alfio Quarteroni; Giuseppe Vergara (Medical & Biological Engineering & Computing, 2014)

Emission of air pollutants from burning candles with different composition in indoor environments - Marco Derudi; Simone Gelosa; Andrea Sliepcevich; Andrea Cattaneo; Domenico Cavallo; Renato Rota; Giuseppe Nano (Environmental Science and Pollution Research, 2014)

Preliminary evaluation of probiotic potential of Lactobacillus plantarum strains isolated from Italian food products - Barbara Turchi; Simone Mancini; Filippo Fratini; Francesca Pedonese; Roberta Nuvoloni; Fabrizio Bertelloni; Valentina Virginia Ebani; Domenico Cerri (World Journal of Microbiology and Biotechnology, 2013)

8-Isoprostane, prostaglandin E2, C-reactive protein and serum amyloid A as markers of inflammation and oxidative stress in antiphospholipid syndrome: a pilot study - Savino Sciascia; Dario Roccatello; Maria Tiziana Bertero; Debora Di Simone; Domenico Cosseddu; Antonella Vaccarino; Mario Bazzan; Daniela Rossi; Cesar Garcia-Fernandez; Leticia Ceberio; Stefania Stella; Elisa Menegatti; et al. (Inflammation Research, 2012)

Polymorphic NumtS trace human population relationships - Martin Lang; Marco Sazzini; Francesco Maria Calabrese; Domenico Simone; Alessio Boattini; Giovanni Romeo; Donata Luiselli; Marcella Attimonelli; Giuseppe Gasparre (Human Genetics, 2012)

Italian accelerometric archive: geological, geophysical and geotechnical investigations at strong-motion stations - Lucia Luzi; Sara Lovati; Ezio D’Alema; Simone Marzorati; Domenico Di Giacomo; Salomon Hailemikael; Ettore Cardarelli; Michele Cercato; Gerarda Di Filippo; Giuliano Milana; Giuseppe Di Giulio; Mario Rainone; et al. (Bulletin of Earthquake Engineering, 2010)